2D‐Organic Layered Materials: Atomically dispersed Fe in a C2N Based Catalyst as a Sulfur Host for Efficient Lithium–Sulfur Batteries (Adv. Energy Mater. 5/2021). Issue 5 (4th February 2021) - Liang, Zhifu; Yang, Dawei; Tang, Pengyi; Zhang, Chaoqi; Jacas Biendicho, Jordi; Zhang, Yi; Llorca, Jordi; Wang, Xiang; Li, Junshan; Heggen, Marc; David, Jeremy; Dunin‐Borkowski, Rafal E.; et al.
Abstract : In article number 2003507, Yingtang Zhou, Andreu Cabot, Jordi Arbiol and co‐workers load single iron atoms into a 2D organic layered material (C2 N) allowing a new route for the development of high performance cathodes for lithium–sulfur batteries.